Catalyst for improving selectivity of CO in reverse water gas as well as preparation method and application of catalyst
By reducing gallium nitrate and nickel with glucose during the preparation of the catalyst and doping metal gallium, the problems of poor stability and decreased activity of Ni-based catalysts in the reverse water gas transformation reaction are solved, and high CO selectivity and long-term stability are achieved.
Patent Information
- Application Number
- CN202510091485.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-21
- Publication Date
- 2025-04-11
AI Technical Summary
The existing Ni-based catalysts have problems of poor stability and reduced activity in the reverse water gas transformation reaction, especially at high temperatures, which leads to agglomeration sintering of the catalyst and reduced CO selectivity.
By adding glucose as a reducing agent during the preparation process, the gallium nitrate and nickel nitrate are reduced to metal gallium and metal nitrate, and partial zirconium dioxide is reduced to oxygen vacancies and doped with metal gallium to improve the dispersion and thermal stability of nickel, NixGay/ZrO2@NC catalyst is prepared.
The catalyst exhibits excellent CO selectivity and stability in the counterwater gas transformation reaction, which can reach more than 95%, and remains active during the catalytic reaction of 100 hours, avoiding the agglomeration and sintering of the catalyst.
Smart Images

Figure CN119793472A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of catalysts, and in particular to a catalyst for improving the selectivity of CO in reverse water gas, a preparation method and application thereof. Background Art
[0002] Over the past few centuries, the widespread use of carbon-rich fossil fuels (such as coal, oil, and natural gas) has driven the development and prosperity of human society. However, this has also led to the emission of a large amount of greenhouse gases (mainly CO2). Before the Industrial Revolution, the concentration of CO2 in the atmosphere was about 280ppm, but by 2018, this value had risen to 390ppm and is expected to reach 570ppm by the end of this century. The transportation industry is the second largest source of greenhouse gas emissions, second only to the energy sector. For example, in the United States, emissions from the transportation industry account for 27% of the total greenhouse gas emissions caused by human activities. The increase in CO2 emissions has led to rising global temperatures, forming a "greenhouse effect", which in turn has caused environmental problems such as rising sea levels and melting glaciers. Therefore, reducing CO2 emissions and developing an effective CO2 capture and utilization system have become the focus of global attention. At present, the utilization of CO2 mainly includes circulation, storage, and conversion. Although circulation and storage can reduce the CO2 content in the atmosphere, they cannot fundamentally reduce the total CO2 reserves, so the conversion of CO2 has become the focus of research. As an economical, safe and renewable carbon source, CO2 is an important resource for the manufacture of organic chemicals, materials and C1 compounds.
[0003] Among the many CO2 conversion methods, the hydrogenation reaction of CO2 has attracted much attention due to its high efficiency. These hydrogenation reactions can produce a variety of products, including methane (CH4), carbon monoxide (CO), ethanol (C2H6O), formic acid (CH2O2) and heavier hydrocarbons. Among these hydrogenation reactions, the reverse water gas shift reaction (RWGS: CO2+H2=CO+H2O, ΔH=40.6kJ / mol) is considered to be a promising method for producing CO chemical raw materials.
[0004] Among many catalysts, Ni-based catalysts have attracted much attention due to their low cost and excellent catalytic performance. However, although Ni-based catalysts show high activity and CO selectivity in the reverse water-gas shift reaction, their stability at high temperatures is poor, and Ni particles are prone to aggregation, resulting in a decrease in catalyst activity, limiting their application in long-term use. In order to improve the performance of Ni-based catalysts in the reaction, researchers have turned their attention to the study of multi-metal doped catalysts. By combining Ni with other metals (such as Cu, Pt, Re, etc.) to form bimetallic or multi-metallic catalysts, the stability and activity of the catalyst can be effectively improved.
[0005] Reference 1 (Feng Yifei, et al. Elucidating the structure-activity relationship of the bimetallic Ni-Cu catalysts for CO2 hydrogenation. Journal of CO2 Utilization, 2024, 80, 102683, doi: 10.1016 / j.jcou.2024.102683.) By combining Cu with Ni, the reducibility of the catalyst can be enhanced to form a stable alloy structure, thereby improving the selectivity for CO and inhibiting the production of CH4.
[0006] In addition, by rationally designing and optimizing the composition and structure of multi-metal catalysts, the performance of the catalyst in the reverse water-gas shift reaction can be further improved. The Chinese patent document with publication number CN116351428A discloses a preparation method and application of a supported catalyst A / MO2-X for the reverse water-gas shift reaction, wherein the composition of the catalyst includes: an active component A, an auxiliary agent X, and an oxide carrier MO2, wherein the active component A is nickel, cobalt or platinum, the auxiliary agent X is potassium or sodium, and the carrier MO2 is cerium oxide, titanium oxide or zirconium oxide. These studies show that multi-metal doping is an effective strategy to improve the performance of Ni-based catalysts and has broad application prospects.
[0007] Since the RWGS reaction is an endothermic reaction, the reaction rate and conversion rate will increase with the increase of temperature. However, too high a temperature will lead to the agglomeration and sintering of the catalyst and the reduction of catalytic activity and CO selectivity, which will lead to the inability to proceed with the reaction. Therefore, it is urgent to find a preparation method that avoids the agglomeration and sintering of the catalyst during practical application, and the prepared catalyst has better catalytic performance. Summary of the invention
[0008] In order to solve the above technical problems, the present invention provides a method for preparing a catalyst for improving the selectivity of CO in reverse water gas. In the method, glucose is added as a reducing agent during the preparation process, gallium nitrate and nickel nitrate are reduced to metallic gallium and metallic nickel, respectively, and part of zirconium dioxide is reduced to produce oxygen vacancies. Metal Ga can improve the dispersion of metallic Ni and enhance the thermal stability of the catalyst, inhibit the agglomeration and sintering of nickel particles, and the prepared catalyst has excellent catalytic performance. In actual application, it does not need to be reduced before use, which reduces steps and reduces energy consumption.
[0009] A method for preparing a catalyst for improving the selectivity of CO in reverse water gas comprises the following steps:
[0010] Gallium nitrate, nickel nitrate and zirconium dioxide are mixed with water and heated, and glucose is added and stirred continuously. After drying, a carbonization reaction is carried out at a high temperature to obtain a catalyst for improving CO selectivity.
[0011] The present invention uses glucose as a reducing agent to reduce gallium nitrate and nickel nitrate to metallic gallium and metallic nickel respectively, so that the catalyst does not need to be reduced before use, reducing the steps of use and reducing energy consumption. At the same time, part of the zirconium dioxide is reduced to generate oxygen vacancies, which can enhance the adsorption and activation of CO2. The doping modification of Ga can induce the distortion of the zirconium dioxide lattice, which will change the arrangement and stability of oxygen ions in the lattice, thereby promoting the formation of oxygen vacancies.
[0012] The catalyst (i.e., Ni x Ga y / ZrO2@NC catalyst) is prepared by doping metallic gallium on the nickel base. The metallic gallium and metallic nickel form a bimetallic alloy phase. The strong electronic interaction between Ga and Ni can effectively regulate the electronic structure of metallic Ni, enhance the selectivity for CO, reduce the occurrence of the side reaction CO+2H2=CH4+H2O, weaken the cracking rate of the byproduct methane, and inhibit the formation of carbon deposits. At the same time, metallic Ga can improve the dispersion of metallic Ni and enhance the thermal stability of the catalyst, inhibit the agglomeration and sintering of nickel particles, so that the prepared catalyst maintains stable catalytic activity and catalytic stability.
[0013] Preferably, the molar ratio of nickel nitrate to gallium nitrate is 1:0.5-2.
[0014] In the present invention, the incorporation of Ga forms a strong electronic interaction with the metal Ni, resulting in the transfer of Ni electrons to Ga. By adjusting the Ga content, the electrical structure of Ni can be regulated. The positively charged species Ni δ+ It can promote the main reaction and effectively improve the selectivity for CO, and the CO selectivity can reach more than 95%.
[0015] Preferably, the molar ratio of nickel nitrate to zirconium dioxide is 2 to 4:5.
[0016] Preferably, the molar ratio of nickel nitrate to glucose is 1:7-15.
[0017] The present invention can control the reduction of nickel nitrate, gallium nitrate and zirconium dioxide through the feeding ratio of glucose, ensure partial reduction of zirconium dioxide, generate oxygen vacancies, and the oxygen vacancies can enhance the adsorption and activation of CO2.
[0018] Preferably, the heating reaction temperature is 70-90° C., and the heating time is 8-24 h.
[0019] Preferably, the temperature of the carbonization reaction is 600-800° C., and the reaction time is 2-4 hours.
[0020] During the carbonization reaction, nickel nitrate and gallium nitrate can be reduced to metallic nickel and metallic gallium, and oxygen vacancies are generated after a portion of zirconium dioxide is reduced. The temperature and time of the carbonization reaction can be controlled to control the degree of reduction. The carbonization reaction of the present invention is close to the temperature of the existing roasting method, but the prepared catalyst has no obvious agglomeration and sintering phenomenon during the actual application process, thereby improving the catalytic activity and selectivity of the catalyst in the reverse water gas shift reaction.
[0021] The present invention also provides a catalyst for improving the selectivity of CO in reverse water gas obtained by the above preparation method. The catalyst can be used without being reduced first, thus reducing the steps of use and lowering energy consumption. It has high catalytic activity and selectivity for the reverse water gas shift reaction and is not deactivated after 100 hours of use, thus having prospects for industrial application.
[0022] The present invention also provides an application of the above-mentioned catalyst in a reverse water-gas shift reaction, and the method of use comprises the following steps: firstly filling the catalyst into a fixed bed reactor, firstly filling the catalyst into a fixed bed reactor, heating the temperature to the reaction temperature, introducing carbon dioxide and hydrogen to carry out a reverse water-gas shift reaction to obtain carbon monoxide.
[0023] Preferably, the CO selectivity of the catalyst is >95%.
[0024] Compared with the prior art, the present invention has the following beneficial effects:
[0025] The present invention uses glucose as a reducing agent to reduce gallium nitrate and nickel nitrate to metallic gallium and metallic nickel, respectively, so that the catalyst does not need to be reduced before use, reducing the steps of use and reducing energy consumption. At the same time, part of the zirconium dioxide is reduced to generate oxygen vacancies, which can enhance the adsorption and activation of CO2. The doping modification of Ga can induce the distortion of the zirconium dioxide lattice, which will change the arrangement and stability of oxygen ions in the lattice, thereby promoting the formation of oxygen vacancies. The prepared catalyst has no obvious agglomeration and sintering phenomenon during actual application, thereby improving the catalytic activity and selectivity of the catalyst in the reverse water-gas shift reaction. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is a transmission electron microscope image of the NiGa / ZrO2@NC catalyst prepared in Example 1.
[0027] Figure 2 XRD spectra of the NiGa / ZrO2@NC catalyst prepared in Example 1 and the Ni / ZrO2@NC catalyst prepared in Comparative Example 2.
[0028] Figure 3 Graph showing the CO2 conversion rates of the catalysts prepared in Examples 1 to 3 and Comparative Examples 1 to 5.
[0029] Figure 4 Graph showing the CO selectivity of the catalysts prepared in Examples 1 to 3 and Comparative Examples 1 to 5. DETAILED DESCRIPTION
[0030] The present invention will be further described in detail below in conjunction with the examples, but the embodiments of the present invention are not limited to the following examples.
[0031] The raw materials used in the present invention are all commercially available.
[0032] Embodiment 1:
[0033] 0.872 g nickel nitrate powder (3 mmol), 0.767 g gallium nitrate powder (3 mmol), and 0.617 g zirconium dioxide powder (5 mmol) were weighed and put into 150 mL deionized water. After stirring at room temperature for 30 min, the mixture was heated to 80 °C in an oil bath. 5.405 g glucose (30 mmol) was slowly added to the beaker and stirred for more than 8 h to evaporate the water. The mixture was then dried in a drying oven at 100 °C for 12 h, placed in a tubular furnace, and heated to 600 °C at a heating rate of 5 °C / min under an Ar atmosphere (40 mL / min). The mixture was carbonized for 3 h and cooled to room temperature to finally prepare the NiGa / ZrO2@NC catalyst.
[0034] Example 2
[0035] 0.581 g nickel nitrate powder (2 mmol), 1.023 g gallium nitrate powder (4 mmol), and 0.617 g zirconium dioxide powder (123.22 5 mmol) were weighed and put into 150 mL deionized water. After stirring at room temperature for 30 min, the oil bath was heated to 80 °C, and 5.405 g glucose (180.1630 mmol) was slowly added to the beaker and stirred for more than 8 h to evaporate the water. Then, the mixture was dried in a drying oven at 100 °C for 12 h, placed in a tubular furnace, and heated to 600 °C at a heating rate of 5 °C / min under Ar atmosphere (40 mL / min), carbonized for 3 h, and cooled to room temperature to finally prepare the NiGa2 / ZrO2@NC catalyst.
[0036] Example 3
[0037] 1.163 g nickel nitrate powder (4 mmol), 0.511 g gallium nitrate powder (2 mmol), and 0.617 g zirconium dioxide powder (5 mmol) were weighed and put into 150 mL deionized water. After stirring at room temperature for 30 min, the mixture was heated to 80 °C in an oil bath. 5.405 g glucose (30 mmol) was slowly added to the beaker and stirred for more than 8 h to evaporate the water. The mixture was then dried in a drying oven at 100 °C for 12 h, placed in a tubular furnace, and heated to 600 °C at a heating rate of 5 °C / min under an Ar atmosphere (40 mL / min). The mixture was carbonized for 3 h and cooled to room temperature to finally prepare the Ni2Ga / ZrO2@NC catalyst.
[0038] Comparative Example 1
[0039] 0.767 g of gallium nitrate powder (3 mmol) and 0.617 g of zirconium dioxide powder (5 mmol) were weighed and put into 150 mL of deionized water. After stirring at room temperature for 30 min, the mixture was heated to 80 °C in an oil bath. 5.405 g of glucose (30 mmol) was slowly added to the beaker and stirred for more than 8 h to evaporate the water. The mixture was then dried in a drying oven at 100 °C for 12 h and placed in a tubular furnace. The temperature was raised to 600 °C at a heating rate of 5 °C / min under an Ar atmosphere (40 mL / min). The mixture was carbonized for 3 h and cooled to room temperature to finally prepare the Ga / ZrO2@NC catalyst.
[0040] Comparative Example 2
[0041] 0.872 g nickel nitrate powder (3 mmol) and 0.617 g zirconium dioxide powder (5 mmol) were weighed and put into 150 mL deionized water. After stirring at room temperature for 30 min, the mixture was heated to 80 °C in an oil bath. 5.405 g glucose (30 mmol) was slowly added to the beaker and stirred for more than 8 h to evaporate the water. The mixture was then dried in a drying oven at 100 °C for 12 h and placed in a tubular furnace. The temperature was raised to 600 °C at a heating rate of 5 °C / min under an Ar atmosphere (40 mL / min). The mixture was carbonized for 3 h and cooled to room temperature to finally prepare the Ni / ZrO2@NC catalyst.
[0042] Comparative Example 3
[0043] 0.872 g nickel nitrate powder (3 mmol), 0.767 g gallium nitrate powder (3 mmol), and 0.510 g aluminum oxide powder (5 mmol) were weighed and put into 150 mL deionized water. After stirring at room temperature for 30 min, the mixture was heated to 80 °C in an oil bath. 5.405 g glucose (30 mmol) was slowly added to the beaker and stirred for more than 8 h to evaporate the water. The mixture was then dried in a drying oven at 100 °C for 12 h, placed in a tubular furnace, and heated to 600 °C at a heating rate of 5 °C / min under an Ar atmosphere (40 mL / min). The mixture was carbonized for 3 h and cooled to room temperature to finally prepare the NiGa / Al2O3@NC catalyst.
[0044] Comparative Example 4
[0045] 0.872 g nickel nitrate powder (3 mmol) and 0.510 g aluminum oxide powder (5 mmol) were weighed and put into 150 mL deionized water. After stirring at room temperature for 30 min, the mixture was heated to 80 °C in an oil bath. 5.405 g glucose (30 mmol) was slowly added to the beaker and stirred for more than 8 h to evaporate the water. The mixture was then dried in a drying oven at 100 °C for 12 h and placed in a tubular furnace. The temperature was raised to 600 °C at a heating rate of 5 °C / min under an Ar atmosphere (40 mL / min). The mixture was carbonized for 3 h and cooled to room temperature to finally prepare the Ni / Al2O3@NC catalyst.
[0046] Comparative Example 5
[0047] 0.872 g of nickel nitrate powder (3 mmol), 0.767 g of gallium nitrate powder (3 mmol), and 0.617 g of zirconium dioxide powder (5 mmol) were weighed and put into 150 mL of deionized water. After stirring at room temperature for 30 min, the mixture was dried in a 100 °C drying oven for 12 h, placed in a muffle furnace, and heated to 300 °C at a heating rate of 5 °C / min under Ar atmosphere (40 mL / min). The mixture was calcined for 1 h, then heated to 500 °C at the same rate, calcined for 3 h, and cooled to room temperature to finally prepare the NiGa / ZrO2 catalyst.
[0048] Sample analysis
[0049] 1. Transmission electron microscopy image analysis
[0050] A transmission electron microscope image of the NiGa / ZrO2@NC catalyst prepared in Example 1 was taken.
[0051] Figure 1This is a transmission electron microscope image of the NiGa / ZrO2@NC catalyst prepared in Example 1. As shown in the elemental diagram, the distribution of Ni, Ga, Zr, and O elements was observed, confirming the successful doping of Ga. In particular, the positions of Ni nanoparticles and Ga nanoparticles are almost consistent, proving the formation of GaNi alloy.
[0052] 2. XRD analysis
[0053] The NiGa / ZrO2@NC catalyst prepared in Example 1 and the Ni / ZrO2@NC catalyst prepared in Comparative Example 2 were subjected to XRD analysis.
[0054] Figure 2 The XRD spectra of the NiGa / ZrO2@NC catalyst prepared in Example 1 and the Ni / ZrO2@NC catalyst prepared in Comparative Example 2 are shown in the figure. As shown in the figure, both catalysts show obvious ZrO2 carrier diffraction peaks. In addition, the Ni / ZrO2@NC catalyst shows obvious metal Ni diffraction peaks, while the NiGa / ZrO2@NC catalyst shows obvious GaNi alloy phase diffraction peaks, proving that Ga is successfully doped and forms an alloy with Ni. However, due to the extremely low content of carbon species on the catalyst, no diffraction peaks related to carbon species were observed.
[0055] 3. Catalyst Performance Analysis
[0056] The catalytic activity of the prepared catalyst was tested using a normal pressure quartz tube fixed bed reactor (8 mm inner diameter, 40 mm length). 0.1 g of catalyst (30-60 mesh) was weighed and loaded into the reactor. Both ends were fixed by quartz wool, and the catalyst bed temperature was measured by a K-type thermocouple. For the catalyst carbonized by glucose, N2 (30 mL / min) was introduced into the reactor after it was loaded into the reactor, and heated to a reaction temperature of 750°C at a heating rate of 10°C / min, and then the reaction gas was switched, and the volume ratio of the reaction gas was V(N2) / V(CO2) / V(H2)=60 / 10 / 10 (flow rate 80 mL / min). After 0.5 h of reaction, the tail gas was condensed by a cold trap and entered the in-situ online gas chromatography for analysis to calculate the conversion rate of CO2 and the selectivity of CO. The reaction time was 100 h. However, for NiGa / ZrO2 catalyst, it needs to be reduced at 750℃ for 2h with reducing gas of V(N2) / V(H2)=9 / 1 (flow rate 30mL / min) before the reaction. After reduction, the reaction gas is switched to carry out the catalytic reaction. The reaction gas is condensed by a cold trap and then enters the in-situ online gas chromatography for analysis to obtain the CO2 conversion rate and CO selectivity. The results are as follows: Figure 3 , Figure 4 And as shown in Table 1.
[0057] Table 1: Catalytic activities of the catalysts prepared in Examples 1 to 3 and Comparative Examples 1 to 5
[0058]
[0059] Figure 3 and Figure 4 The CO2 conversion rate and CO selectivity of the catalysts prepared in Examples 1 to 3 and Comparative Examples 1 to 5 are shown in FIG. Figure 3 , Figure 4 As shown in Table 1, the Ni prepared in Examples 1 to 3 x Ga y The / ZrO2@NC catalyst can still show high catalytic activity during the 100h catalytic reaction, and its CO selectivity can reach more than 95%. The experimental results show that the doping modification of metal Ga can significantly improve the catalytic activity and catalytic stability of nickel-based catalysts. This is because the addition of Ga can improve the dispersion of Ni and enhance the thermal stability of the catalyst, thereby improving the catalytic activity and catalytic stability. In addition, the catalytic activity of the Ga / ZrO2@NC catalyst with a single Ga load is very low, proving that Ni is the main catalytic active site of the reverse water gas shift reaction.
[0060] At the same time, Ni x Ga y From the catalytic activities of Ga / ZrO2@NC series catalysts, Ga / ZrO2@NC and Ni / ZrO2@NC catalysts, it can be inferred that by doping with metallic Ga, the electronic interaction between Ga and Ni is enhanced, the electronic structure of Ni is effectively regulated, the selectivity for CO is enhanced, and the occurrence of methanation side reactions is suppressed, avoiding carbon deposition due to the cracking of the by-product CH4.
[0061] By comparing the catalytic activities of NiGa / ZrO2@NC catalyst and NiGa / Al2O3@NC catalyst, it is found that Ga doping can induce lattice distortion of ZrO2, resulting in the formation of more surface oxygen vacancies, thereby increasing the adsorption and activation of CO2 to improve the catalytic activity; however, since the Al2O3 carrier has Lewis acidic characteristics and no oxygen vacancies are formed, the adsorption and activation of CO2 in the reaction are inhibited, resulting in a decrease in activity.
[0062] Although the NiGa / ZrO2 catalyst prepared by the existing calcination method can show excellent selectivity and conversion rate after 3 hours of reaction, the activity decreases rapidly and becomes deactivated due to the agglomeration and sintering of metal particles on the catalyst surface under high temperature reaction.
[0063] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention is described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a catalyst for improving CO selectivity in reverse water gas, characterized in that: The following steps are involved: Gallium nitrate, nickel nitrate and zirconium dioxide are mixed with water and heated, and glucose is added and stirred continuously. After drying, a carbonization reaction is carried out at a high temperature to prepare a catalyst for improving the selectivity of CO in reverse water gas.
2. The method for preparing a catalyst for improving CO selectivity in reverse water gas according to claim 1, characterized in that: The molar ratio of the nickel nitrate to the gallium nitrate is 1:0.5-2.
3. The method for preparing a catalyst for improving CO selectivity in reverse water gas according to claim 1, characterized in that: The molar ratio of nickel nitrate to zirconium dioxide is 2-4:
5.
4. The method for preparing a catalyst for improving CO selectivity in reverse water gas according to claim 1, characterized in that: The molar ratio of the nickel nitrate to the glucose is 1:7-15.
5. The method for preparing a catalyst for improving CO selectivity in reverse water gas according to claim 1, characterized in that: The heating reaction temperature is 70-90° C., and the heating time is 8-24 hours.
6. The method for preparing a catalyst for improving CO selectivity in reverse water gas according to claim 1, characterized in that: The temperature of the carbonization reaction is 600-800° C., and the reaction time is 2-4 hours.
7. A catalyst for improving the selectivity of CO in reverse water gas, prepared according to the preparation method according to any one of claims 1 to 6.
8. Use of the catalyst for improving CO selectivity in reverse water gas according to claim 7 in reverse water gas shift reaction.
9. The use according to claim 8, characterized in that: The CO selectivity of the catalyst is >95%.
10. The use according to claim 8, wherein the method for using the catalyst in the reverse water gas shift reaction comprises the following steps: firstly, the catalyst is filled into a fixed bed reactor, heated to the reaction temperature, and carbon dioxide and hydrogen are introduced to perform a reverse water gas shift reaction to obtain carbon monoxide.
Citation Information
Patent Citations
Preparation and application of reverse water gas shift catalyst taking sodium and potassium as auxiliaries
CN116351428A